2016
DOI: 10.1080/03014460.2016.1202321
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance imaging of third molars: developing a protocol suitable for forensic age estimation

Abstract: Three Tesla MRI of the third molars is a feasible technique for forensic age estimation, in which a T2 FSE sequence can provide the desired in plane resolution within a clinically acceptable acquisition time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) provides a valuable tool for the localization of impacted teeth (Tymofiyeva, Rottner, Jakob, Richter, & Proff, ). MRI of impacted third molars is a well‐established technique (Ferretti, Malventi, & Malasoma, ) in dental magnetic resonance imaging, and there is an increasing use in forensic radiology (De Tobel, Hillewig, Bogaert, Deblaere, & Verstraete, ). The spatial resolution of the sequences used in the present study is superior to the spatial resolution used by Ferretti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) provides a valuable tool for the localization of impacted teeth (Tymofiyeva, Rottner, Jakob, Richter, & Proff, ). MRI of impacted third molars is a well‐established technique (Ferretti, Malventi, & Malasoma, ) in dental magnetic resonance imaging, and there is an increasing use in forensic radiology (De Tobel, Hillewig, Bogaert, Deblaere, & Verstraete, ). The spatial resolution of the sequences used in the present study is superior to the spatial resolution used by Ferretti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Results described in this manuscript were orally presented at the 6 th International Society of Forensic Part of the study population has been included in previous papers to study the development of their clavicles, without a specific focus on motion artefacts: [1][2][3][4][5][6][7][8]. Most protocols will include a method of fixation or stabilisation of the region of interest, since MRI acquisition requires several minutes and is prone to motion artefacts.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the wrist can be fixed with a flexible cloth belt [9] or stabilised in the coil using pillows [10] or a vacuum bed [11]. The head can be fixed by an individualised bite plate [2]. This minimises motion artefacts that might impede an adequate assessment of the developmental stage of the considered anatomical structure.…”
Section: Related Workmentioning
confidence: 99%
“…The Graz protocol uses a more rigid coil, so support by pillows is deemed sufficient. Furthermore, De Tobel et al (2017) suggested that an in-plane resolution of 0.33 x 0.33 mm² is necessary to discern the stages of apical closure [17]. However, their study sample was small with only 10 participants and their suggestion was based on only one case.…”
Section: Main Text Introductionmentioning
confidence: 96%
“…Although not routinely used in clinical dental practice, dedicated MRI has been demonstrated to adequately depict periodontal space, apical foramen, cortical and trabecular bone [13,14]. To our knowledge dental age estimation by third molars MRI has only been studied by three research groups [9,[15][16][17][18][19]. Guo et al (2015) described an MRI protocol for a 3T Philips scanner, while Baumann et al (2015) and De Tobel et al (2017) used a 3T Siemens scanner.…”
Section: Main Text Introductionmentioning
confidence: 99%